TRPC3 channels play a critical role in the theta component of pilocarpine‐induced status epilepticus in mice. (24th December 2016) - Phelan, Kevin D.; Shwe, U Thaung; Cozart, Michael A.; Wu, Hong; Mock, Matthew M.; Abramowitz, Joel; Birnbaumer, Lutz; Zheng, Fang
Summary: Objective: Canonical transient receptor potential (TRPC) channels constitute a family of cation channels that exhibit a regional and cell‐specific expression pattern throughout the brain. It has been reported previously that TRPC3 channels are effectors of the brain‐derived neurotrophic factor (BDNF)/trkB signaling pathway. Given the long postulated role of BDNF in epileptogenesis, TRPC3 channels may be a critical component in the underlying pathophysiology of seizure and epilepsy. In this study, we investigated the precise role of TRPC3 channels in pilocarpine‐induced status epilepticus (SE). Methods: The role of TRPC3 channels was investigated using TRPC3 knockout (KO) mice and TRPC3‐selective inhibitor Pyr3. Video and electroencephalography (EEG) recording of pilocarpine‐induced seizures were performed. Results: We found that genetic ablation of TRPC3 channels reduces behavioral manifestations of seizures and the root‐mean‐square (RMS) power of SE, indicating a significant contribution of TRPC3 channels to pilocarpine‐induced SE. Furthermore, the reduction in SE in TRPC3KO mice is caused by a selective attenuation of pilocarpine‐induced theta activity, which dominates both the preictal phase and SE phase. Pyr3 also caused a reduction in the overall RMS power of pilocarpine‐induced SE and a selective reduction in the theta activity during SE. Significance: Our results demonstrate that TRPC3 channels unequivocally contribute to pilocarpine‐induced SE and could be a novel molecular target for new anticonvulsive drugs.